EFEKTIFITAS JENIS MEDIA TANAM TERHADAP PERKECAMBAHAN BENIH KACANG TANAH (Arachis hypogea L) - Ashraf Ashraf; Dewi Junita (Universitas Teuku Umar, 2020)
Peanuts (Arachis hypogaea L) are one of staple food after rice. In industry, peanuts used as material for made the cheese,butter, soap and cooking oil. For optimal growth of peanuts need the optimal condition, growing media are one of external factors who influence the growth of peanuts seed. This research was aimed to determine the various growing media on germination of peanut seeds. This research was implemented at UPTD BPSB Provinsi Aceh laboratory. Thisexperiment was conducted in a completely randomized design (CRD) with the sand media, cocopeat, husk media, husk charchoal, and sand malang as factors. The result showed that the growing media treatment affected the growth of germination peanut seeds. Cocopeat media was showed the better result of germination percentage and vigour index compared other treatment. The avarage of germination percentage and vigour index were 96% and 67,5%. Husk media showed the lower result based on the observed variables. Keyword : Peanuts, Growing Media, Germination